Conceptualization and Perspectives on Social Media Effects on Online Political Participation: A Review (Journal of Management and Social Sciences, 2019)
Social science phenomena are regularly faced with a myriad of debate among whichare the issues of conceptualization and perspectives. These differing views come aboutas a result of differences in the scope, operationalization, methodology, objectives,time or socio cultural context of exiting social science researches. Expectedly, theconcept of online political participation on social media in the digital age has also beenaffected by these debates. Social media has rapidly been adopted as a tool for politicalparticipation because online opportunities for such participation have become animportant avenue for citizens’ engagement in democracies. Consequently, increasingnumber of researches are being carried out in this area, thus creating differing views interms of definitions and perspectives of the phenomena online political participation onsocial media. As a consequence, this paper attempts to elucidate arguments on theseviews by reviewing some existing studies in this area with a view to providing a clearunderstanding of this form of political participation on social media.